Illusions of techno-nationalism - Luo, Yadong (Journal of International Business Studies, 2022)
Current techno-nationalism presents new risks in international business, amplifying volatility, uncertainty, and complexity for multinational enterprises (MNEs). This study explains how today’s techno-nationalism differs from its traditional form, the underlying theoretic logic, the damage it may cause to MNEs, and what MNEs can do to contain the potential harm. We elaborate on several points: (1) new techno-nationalism combines geopolitical, economic, national security, and ideological considerations, and is thus more complex and disruptive to international business than the traditional standpoint; (2) new techno-nationalism is underpinned by the realism doctrine, which portrays the world as zero-sum competition in which states leverage their power of economic coercion, and does not recognize the importance of technological interconnectivity, resource complementarity, open innovation, and positive-sum co-opetition; (3) techno-nationalism obstructs MNEs, especially those dependent on the global technology supply chain and on target country market contribution; and (4) MNEs can respond to techno-nationalism, defensively or offensively, contingent upon their exposure and ability to manage the risks associated with related policies.